7 Platelet rich plasma for acute achilles tendon rupture: a double-blind, multicentre, randomised, placebo-controlled trial. (April 2019) - Keene, David; Alsousou, Joseph; Harrison, Paul; Hulley, Philippa; Wagland, Susan; Parsons, Scott; Thompson, Jacqueline; O'Connor, Heather; Schlüssel, Michael; Dutton, Susan; Lamb, Sarah; Willett, Keith
Abstract : Introduction: Platelet Rich Plasma (PRP), an autologous supraphysiological concentration of platelets from whole blood, has demonstrated positive cellular and physiological effects on healing in the laboratory. However, evidence from robust clinical trials is lacking. We aimed to determine the clinical efficacy of PRP for treating acute Achilles tendon rupture. Materials and methods: 230 adults starting non-surgical management within 12 days of rupture were randomised to PRP injection or dry needle insertion, under local anaesthetic. Participants were blinded and received standardised rehabilitation. Blinded outcome assessments were at 4, 7, 13, and 24 weeks. Primary outcome: muscle-tendon function assessed by work performed during the heel-rise endurance test (HRET), measured with the Limb Symmetry Index (LSI, 0%–100%) at 24 weeks. Secondary outcomes: Achilles Tendon Rupture Score (ATRS), quality of life, pain and goal attainment. Results: Of 230 participants, 114 were allocated to PRP injection (103 received PRP), 116 were allocated to and received placebo. At 24 weeks, 201/230 (87%) completed the HRET and 214/230 (93%) completed patient-reported outcomes. Participant characteristics between the groups were similar. There was no difference between groups at 24 weeks in LSI (mean difference=−4.373; 95% CI −11.217, 2.471; p=0.195). There were no differences in the secondary outcomes and adverse event rates. Conclusion: This study design and standardised PRP preparation secure robust clinical trial evidence for PRP in managing Achilles tendon rupture, and suggest that PRP offers no patient benefit. Use of PRP in soft tissue injuries must be questionable unless supported by equally robust evidence indicating positive outcomes.